Efficiency measurement of pharmaceutical industry using the malmquist total productivity index - Doraisamy, S.M.; Azad, A.K. (2014)
The pharmaceutical industry of Bangladesh is now meeting around 97% of total domestic demand with an annual two digit growth rate. But the question arises as to whether the firms produce efficiently? The paper measures technical efficiency of the pharmaceutical industry of Bangladesh using Data Envelopment Analysis (DEA) over a period of 2009 to 2013. We use the non-parametric DEA with one output- annual sales and three inputs; viz. (i) fixed asset; (ii) raw material cost; and (iii) cost of salary. Results of the analysis reveal that Malmquist total factor productivity index (TPI) has maintained a slightly upward trend during the study period with a value of 4.7% annually. It has also been observed that the major contributor of TPI growth is technological change with a value of 10.8% positive growth annually. Additionally, all changes of technical efficiency; pure efficiency and scale efficiency have regressed with values of 5.5%, 2.1% and 3.5% respectively. The overall productivity progress was due to technological progress and an overall efficiency regress. Thus, the gains in productivity are entirely due to technological advancements, and not efficiency improvement. The main source of inefficiency in pharmaceutical industry is scale inefficiency rather than pure technical inefficiency.